PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN NASABAH DALAM MENGGUNAKAN TABUNGAN IB HASANAH PADA PT. BNI SYARIAH CABANG PALU - FAISAL, IMAN AGUS (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
The research aims to find out the influence of mix promotion on customer decision in using iB Hasanah saving at PT. BNI Syariah Branch Palu. The variable used are advertisement (X1), selling promotion (X2), relationship between people (X3), personal selling (X4), direct marketing (X5), as well as variable customer decision (Y). This is a quantitative research. Sample consists of 72 respondents who are the customers of iB Hasanah saving at PT. BNI Syariah Branch Palu. Method of analysis is multiple linear regressions. The research results indicate that variable of mix promotion simultaneously affect on customer decision. Advertisement partially affect on customer decision, while selling promotion, people relationship, personal selling, and direct marketing partially have non-significant influence on customer decision.